A PLS-SEM Analysis of Emotional Intelligence and Construction Organisation’s Performance Nexus in South Africa - Lerato Millicent Aghimien; Clinton Aigbavboa (Buildings)
Previous research has highlighted the critical role of emotional intelligence (EI) in enhancing employee performance. However, there is a notable gap in studies examining the connection between EI competencies and the performance of construction organisations, employees and overall project outcomes within the South African construction sector. This study analysed the relationship between EI and the performance of construction organisations to enhance project delivery through effective EI management among construction teams. A mixed-method approach was employed, utilising both Delphi techniques and a questionnaire survey. Data collected from construction experts were analysed using various statistical methods, including mean score, the Kruskal–Wallis H-Test, and partial least squares structural equation modelling. The findings, supported by various reliability, validity and fit indices, demonstrate that EI competencies related to self-awareness, self-management and relationship management significantly contribute to the performance of construction organisations. This study enriches the existing body of knowledge on EI by providing a framework that connects EI competencies with organisational performance in the South African construction context, an area that has been largely underexplored.